التطور الاداري لبلدة سيدي عون بوادي سوف (1854-1962م)، على ضوء الرواية الشفوية والمصادر المحلية - صغيري, سفيان (University of Eloued جامعة الوادي, 2022)
عرفت بلدة سيدي عون كغيرها من حواضر سوف وبواديها تطورا في نظام الحكم والادارة المحلية منذ تأسيسها خلال القرن 18م، حيث مرت بنظام الجماعة ثم المشيخة الذي اعتمدته السلطة الفرنسية فيما بعد، بإصدارها عدة مراسيم وقوانين تنظيمية انتهت الى انشاء البلدية بشكل رسمي قبيل الاستقلال. Sidi Aoun, like other cities in Souf and its valleys, has known a development in the system of governance and local administration since its establishment during the 18th century AD, as it passed through the djamaa and then the sheikhdom, which was later adopted by the French authority, by issuing several decrees and organizational laws that ended with the establishment of the municipality formally prior to independence.
مقال